Carbon footprint of robotically‐assisted laparoscopy, laparoscopy and laparotomy: a comparison. Issue 4 (22nd February 2015) - Woods, Demetrius L.; McAndrew, Thomas; Nevadunsky, Nicole; Hou, June Y.; Goldberg, Gary; Yi‐Shin Kuo, Dennis; Isani, Sara
Abstract: Background: To date there have been no comprehensive, comparative assessments of the environmental impact of surgical modalities. Our study seeks to quantify and compare the total greenhouse gas emissions, or 'carbon footprint', attributable to three surgical modalities. Methods: A review of 150 staging procedures, employing laparotomy (LAP), conventional laparoscopy (LSC) or robotically‐assisted laparoscopy (RA‐LSC), was performed. The solid waste generated (kg) and energy consumed (kWh) during each case were quantified and converted into their equivalent mass of carbon dioxide (kg CO2 e) release into the environment. The carbon footprint is the sum of the waste production and energy consumption during each surgery (kg CO2 e). Results: The total carbon footprint of a RA‐LSC procedure is 40.3 kg CO2 e/patient ( p < 0.01). This represents a 38% increase over that of LSC (29.2 kg CO2 e/patient; p < 0.01) and a 77% increase over LAP (22.7 kg CO2 e/patient; p < 0.01). Conclusions: Our results provide clinicians, administrators and policy‐makers with knowledge of the environmental impact of their decisions to facilitate adoption of sustainable practices. Copyright © 2015 John Wiley & Sons, Ltd.